Wakaf Untuk Pembangunan Infrastruktur Negara Dalam Persepektif Hukum Islam - Mashuri, Muhammad; Iskandar, M zhafran Nauval; Wulandari, Nina Ramadhani (ASAS, 2022)
The purpose of the research is to analyze the views of Islamic law regarding waqf assets for the development of state infrastructure. The research uses descriptive analytic qualitative or literature research. The objects of this study are literary works in the form of books related to waqf about the development of state infrastructure from an Islamic perspective. Based on the results of the study of waqf for the development of state infrastructure from the perspective of Islamic law, it can be concluded into several points which Waqf provisions for state infrastructure have been determined in Law Number 41 of 2004 in Article 22. In order to achieve the objectives and functions of property waqf, waqf can only be allocated for: facilities and religious activities; facilities for education and health activities; assistance to the poor, neglected children, orphans, and scholarships; progress and improvement of the people's economy; progress of general welfare; and others that do not conflict with sharia and laws and regulations. Waqf for state infrastructure in Islam is permissible because it was adopted during the reign of the Rashidun Khulafaur, namely the Umayyad and Abbasid Dynasties. Keywords: Islamic law, Undang-Undang, Waqf for state infrastructure